The Blockchain's Impact on Digital Marketing Platforms - Alexander Hahn; Timo Knackstedt; Philipp Sandner (Marketing Review St.Gallen, 2020)
The platform economy is booming. However, platform business models are often based on powerful monopolies or oligopolies, leading stakeholders to look for more balanced ecosystems. As blockchain technology offers decentralized solutions, it appears attractive for replacing such platforms. However, many blockchain applications are still in an early stage. This paper scrutinizes how the blockchain affects the platform economy and whether relevant blockchain applications with product/market fit exist. The paper draws on a qualitative mixed-method approach followed by a case analysis to develop a basic framework for assessing the impact of blockchains on platform economies. The results are illustrated by means of a blockchainbased platform with a proven product/market fit. Options for incumbent firms to draw on this new infrastructure are outlined.
Keywords: 650